Dystopian: Resistance to Government Control in the Novel "Red Rising" by Pierce Brown - Tedy Pratama Putra; Rahmi Rivalina (Morphosis: Journal of Literature, 2022)
This study is entitled “Dystopian Resistance on Government Control in the Red Rising Novel by Pierce Brown”. This study aims to discuss the main character’s resistance to government control after all the discrimination and the inequality government regulation that Darrow experienced. Darrow is the main character from the Red class, which is the lowest class on this society. Darrow lost his wife because of the decision of the Government though Eo, Darrow’s wife not being obedient to the ArchGovernor’s Rules. Then, he realized the system that was created by the ArchGovernor is unfair treatment to the society and chose to resist by being the Gold the higher color classes. Darrow disguise as the Gold, observing their strength and weakness, stealing the gold’s sympathy to be the leader and got the power to control the Gold to change the social class system.The essential passages were examined by using Dystopian Theory (Clayes, 2017) by using the qualitative method. The results show that the main character resists government control to fight for equality for the society and himself. Keywords: dystopian, government control, resistance, equality